2005
DOI: 10.1136/jnnp.2003.033324
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormones modulate brain damage in multiple sclerosis: MRI evidence

Abstract: Background: Sex related differences in the course and severity of multiple sclerosis (MS) could be mediated by the sex hormones. Objective: To investigate the relation between serum sex hormone concentrations and characteristics of tissue damage on conventional magnetic resonance imaging (MRI) in men and women suffering from relapsing-remitting MS. Results: Serum testosterone was significantly lower in women with MS than in controls. The lowest levels were found in women with a greater number of gadolinium enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 29 publications
6
95
0
4
Order By: Relevance
“…These studies suggest that androgens are more protective than estrogens in ameliorating EAE. The lowest levels of serum testosterone in women with MS correlate with the severity of the disease, another indication that androgens are protective (Tomassini et al, 2005). Our in vivo CNS studies also demonstrate that glia in the CNS is one axis affected by androgen withdrawal but also raises an intriguing possibility of a direct link between Olg and myelin degeneration and induction of an autoimmune response.…”
Section: Oligodendrocyte Proliferation and Cell Death Is Increased Inmentioning
confidence: 49%
“…These studies suggest that androgens are more protective than estrogens in ameliorating EAE. The lowest levels of serum testosterone in women with MS correlate with the severity of the disease, another indication that androgens are protective (Tomassini et al, 2005). Our in vivo CNS studies also demonstrate that glia in the CNS is one axis affected by androgen withdrawal but also raises an intriguing possibility of a direct link between Olg and myelin degeneration and induction of an autoimmune response.…”
Section: Oligodendrocyte Proliferation and Cell Death Is Increased Inmentioning
confidence: 49%
“…Recently, the same group presented another study of gender-related modulation of pathological changes in RRMS where they related serum sex hormone levels to MRI characteristics of brain lesions in MS. In men, they reported a positive correlation between estradiol concentrations and brain damage as measured by both T1 and T2-lesion load (Tomassini et al, 2005). Greater brain damage, as documented by black holes, was associated with higher testosterone in women and higher estradiol levels in men, indicating that sex hormones (both estradiol and testosterone) are involved in the process leading to irreversible tissue damage, but that their role might differ between the sexes.…”
Section: Discussionmentioning
confidence: 95%
“…Another study has found a significantly higher number of Gd-enhanced lesions in women with abnormally low testosterone levels. In men, estradiol concentration has correlated with the volume of T1 lesions and the contrast-enhanced T2 lesions [138]. These data provide evidence that sex hormones modulate the development of brain tissue damages and repair in MS. Luchetti et al [139] have extended the research in gender differences of steroid synthesis and signaling in the brains of MS patients.…”
Section: Clinical Evidence For the Effects Of Sex Hormones On Diseasementioning
confidence: 53%